Effective control of grassy weeds in wheat with ready mix combination of Pinoxaden + Clodinafop (Traxos 5EC) - Chhokar, Rajender Singh (Journal of Cereal Research, 2025)
Ready mix combination of Pinoxaden 2.53% + Clodinafop- propargyl 2.53% (Traxos 5EC) was evaluated for the control of grassy weeds in wheat. It was very effective in controlling Phalaris minor Retz. (Littleseed canarygrass) and Avena ludoviciana Dur. (Wild oat), but was ineffective for control of broad-leaved weeds. The optimum dose of Traxos 5EC (Pinoxaden2.53% + Clodinafop- propargyl 2.53%) for control of grassy weeds was 50-60 g a.i. /ha The efficacy of Traxos 5EC at 50-60 g a.i./ha having the reduced doses of clodinafop and pinoxaden (25+25 to 30+30 g/ha) in controlling grass weeds in wheat was similar to the recommended rates of clodinafop 60 g/ha, pinoxaden 50 g/ha and fenoxaprop 120 g/ha. The wheat yield among these herbicides was similar and these herbicides provided 83.0-100.9% higher yield compared to untreated weedy check.